Metodología social campesino a campesino como alternativa para la transición agroecológica y la promoción de la diversificación del uso de la tierra en una región minera: un estudio de caso en el cuadrilátero ferrífero de Minas Gerais, Brasil (2023)
The Iron Quadrangle of Minas Gerais, Brazil has suffered disastrous socioeconomic and environmental consequences due to predatory extractive activities such as mining. A diversified development model that takes into account social, cultural, environmental, and institutional factors is urgently needed. This Participatory-Action-Research project aims to promote agroecological territorialization in the peasant communities of Itabirito, Mariana, and Ouro Preto using the Farmer-to-Farmer Social Methodology as an instrument for the project development, to foster economic diversification and sustainable land use, thus strengthening agroecological production.